Phenolic Compounds from Clinopodium urticifolium and Their Antivirus Activities - Pan, Chong; Huang, Jin; Gao, Zherui; Feng, Wen; Yang, Guangyu; Chen, Yegao; Li, Zhong (Asian Journal of Chemistry, 2012)
A new phenolic compound, clinopodphenol B (1), together with six known phenols, were isolated from the whole plant of Clinopodium urticifolium. The structure of 1 was elucidated by spectroscopic methods including extensive 1D and 2D NMR techniques. Compound 1 was also tested for their anti HIV-1 activity and antitobacco mosaic virus activity. The results showed that compound 1 have modest anti HIV-1 activity and anti-tobacco mosaic virus activity, respectively.